Strategi Penguatan Daya Saing Usaha Mikro Sektor Kreatif melalui Integrasi Penilaian Kinerja Finansial dan Non-Finansial: Studi Kasus Bucket Nessflower - Nimatul Izzah; Ni'ma Kamalia; Erlin Wijaya; Juhari Effendi Saputra (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze the performance evaluation of the micro business Bucket Nessflower in Pasuruan City using the Balanced Scorecard (BSC) and Resource-Based View (RBV) approaches. This florist business represents a rapidly growing creative sector among young entrepreneurs but still faces challenges in financial literacy and managerial capabilities. The research employed a qualitative method through literature studies and in-depth interviews using a purposive sampling technique to obtain relevant empirical data. The results show that Bucket Nessflower excels in product innovation and digital marketing strategies, which effectively enhance customer loyalty and expand market reach. However, its main weakness lies in the manual financial recording system, which limits operational efficiency and data-driven decision-making. Through the application of the BSC framework, it was found that business performance needs improvement, particularly in the financial and learning perspectives, to achieve long-term sustainability. In conclusion, the integration of financial literacy, digitalization, and innovation serves as a key factor in building sustainable competitive advantage for micro creative enterprises in the digital economy era.